Endoscopic ultrasound-guided sampling of solid pancreatic masses: 22-gauge aspiration versus 25-gauge biopsy needles. Issue 1 (December 2015) - Yang, Min; Yim, Hyunee; Hwang, Jae; Lee, Dakeun; Kim, Young; Lim, Sun; Kim, Soon; Kang, Joon; Yoo, Byung; Kim, Jin
Abstract Background Biopsy needles have recently been developed to obtain both cytological and histological specimens during endoscopic ultrasound (EUS). We conducted this study to compare 22-gauge (G) fine needle aspiration (FNA) needles, which have been the most frequently used, and new 25G fine needle biopsy (FNB) needles for EUS-guided sampling of solid pancreatic masses. Methods We conducted a retrospective cohort study of all EUS-guided sampling performed between June 2010 and October 2013. During the study period, 76 patients with pancreatic masses underwent EUS-guided sampling with a 22G FNA needle (n  = 38) or a 25G FNB needle (n  = 38) for diagnosis. An on-site cytopathologist was not present during the procedure. Technical success, the number of needle passes, cytological diagnostic accuracy, cytological sample quality (conventional smear and liquid-based preparation), histological diagnostic accuracy, and complications were reviewed and compared. Results There were no significant differences in technical success (100 % for both), the mean number of needle passes (5.05 vs. 5.55, P  = 0.132), or complications (0 % for both) between the 22G FNA group and the 25G FNB group. The 22G FNA and 25G FNB groups exhibited comparable outcomes with respect to cytological diagnostic accuracy (97.4 % vs. 89.5 %, P  = 0.358) and histological diagnostic accuracy (34.2 % vs. 52.6 %, P  = 0.105). In the cytological sample quality analysis, the 25G FNB group exhibited higher scores for the amount of diagnostic cellular material present (22G FNA: 0.92 vs. 25G FNB: 1.32, P  = 0.030) and the retention of appropriate architecture (22G FNA: 0.97 vs. 25G FNB: 1.42, P  = 0.010) in the liquid-based preparation. The 25G FNB group showed a better histological diagnostic yield for specific tumor discrimination compared with the 22G FNA group (60 % vs. 32.4 %, P  = 0.018). Conclusions Use of the 25G FNB needle was technically feasible, safe, efficient, and comparable to use of the standard 22G FNA needle in patients with solid pancreatic masses in the absence of an on-site cytopathologist. The cytological sample quality in the liquid-based preparation and the histological diagnostic yield for specific tumor discrimination of EUS-guided sampling using a 25G FNB needle were significantly higher than those using a 22G FNA needle.